A Descriptive Analysis Of Register Used In Football Championship - ULFIYATI, NINIK (2007)
Language used in football is different from that used by people in daily conversation. There are specific terms to explain the event that happens in the game. Many registers used in Football Championship can be found especially in English. In this case, this research analyzes the form, the real meaning, and the equivalence of register usually used in Football register. The type of this research is descriptive qualitative research. The terms analyzed are Football registers used in football championship in Premier League (England). The object of this research is the language used by all participants on the football championship. The data are terms used by all participants in football championship. The data are taken from Internet, Bola Tabloid and some from sport news in television. In collecting the data, the writer browses website in internet, the writer collects and selects all football terms from football match and internet (football website) and makes notes by choosing and selecting more to make sure that the data collected are registers used in football championship. Based on data analysis, there are three findings of the answer of problem statements. First, the linguistic forms there are found five of linguistic forms: letter, compound word, number, word, and phrase. Second, the meaning of football register terms found are the real meaning and the new meaning can share some features of meaning whereas each of them has different meaning (R∞N), the real meaning is broader than the new meaning (R > N), the real meaning and the new meaning is identical to each other (R≈N), the real meaning and the new meaning is quite different (R ≠ N), the new meaning does not have the real meaning (N). Third, the equivalence of the terms is including the word form, compound word form, and phrase. The equivalence consists of adopting, borrowing, and equivalence.